Microalgae-based food: Purchase intentions and willingness to pay - Natalia Maehle; Frode Skjeret (Future Foods, 2022)
Consumer acceptance is pivotal for the success of new foods, and it is therefore necessary to understand the determinants influencing consumers’ behaviour for microalgae-based food. The current study explores the influence of various factors on consumers’ attitude, purchase intention and willingness to pay for two microalgae-based products (bread and beer). An online survey with a consumer panel (N = 1,011) was conducted, and a structural equation modelling procedure was implemented. The results indicate that environmental concern and subjective norms (i.e., social norms on microalgae-based food) have significant positive effect on consumers’ attitude and purchase intentions towards microalgae-based food. Purchase intentions, attitude towards innovation in food and subjective norms positively and highly significantly impact the willingness to pay for microalgae-based food. Thus, microalgae-based food appeals to the environmentally engaged and innovative consumers. Moreover, the opinions of others play an important role in the acceptance of the microalgae-based food. This study contributes to the emerging stream of literature on microalgae-based food. Understanding which factors influence the purchase behaviour for this food is highly important for its market success. The study provides evidence-based input for practitioners in their efforts to evaluate consumer interest for microalgae-based food and develop effective marketing strategies for its further promotion.